The Influences of Transformational Leaderships on Employees Performance (A Study of the Economics and Business Faculty Employee at University of Muhammadiyah Malang) - Elgelal, Kamel Saleh Khalifa; Noermijati, Noermijati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
This study aims at investigating the effect of direct transformational leadership on employee motivation, jobs satisfaction, and employee performance. Then investigating the effect of direct employee satisfaction and motivation on employee job performance and employee's performance, and to know that job satisfaction gives direct influence on employee performance. Than in this study also investigates the influence of indirect transformational leadership on employee performance through employee motivation and job satisfaction. The research was conducted all employees at FEB UMM. The technique of data collecting used questionnaires with Likert scale, whereas the method of analysis used to answer the purposes of this study was Partial Least Square (PLS).Â The finding of this study reveals that transformational leadership gives positive and significant effect on employee motivation and employees' job satisfaction, but no significant effect found on employee performance. The finding also shows that employee motivation gives positive and significant effect on job satisfaction, but no significant effect on employee performance. Then, job satisfaction also shows positive and significant effect on employee performance. Then, transformational leadership has no significant effect on employee performance through employee motivation, so that employee motivation cannot mediate the effect of transformational leadership on employee performance. While transformational leadership has significant effect on employee performance through job satisfaction, so job satisfaction expressed can mediate the effect of transformational leadership on employee performance.